2011
DOI: 10.4021/cr15w
|View full text |Cite
|
Sign up to set email alerts
|

Markedly Elevated Cardiac Bio-Markers at Presentation With Normal Ventricular Function: A Novel Clinical Subset of Myocarditis Manifestation

Abstract: We present a case of a 19-year-old woman with myocarditis who had significantly elevated cardiac markers at presentation even before any myocardial damage ensued. The patient had complicated clinical course with ventricular arrhythmia and cardiac arrest requiring resuscitation but eventually recovered completely. Though there is limited information available regarding such cases, the significantly elevated initial cardiac markers in the absence of left ventricular decompensation may probably represent a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…For more than a decade, cardiac troponin I (cTnI) is one of the most widely used biomarkers, due to its nearly complete cardiac tissue specificity and its long serum half-life (Babuin and Jaffe 2005, Reichlin et al 2009, Scharnhorst et al 2011). Clinical data indicated that subjects with even minor elevations of cTnI are at increased risk of premature MI (Palla et al 2011). When a patient with chest pain is seen in the emergency room, blood is routinely drawn to detect any rise in cardiac biomarker concentrations due to heart muscle damages.…”
Section: Introductionmentioning
confidence: 99%
“…For more than a decade, cardiac troponin I (cTnI) is one of the most widely used biomarkers, due to its nearly complete cardiac tissue specificity and its long serum half-life (Babuin and Jaffe 2005, Reichlin et al 2009, Scharnhorst et al 2011). Clinical data indicated that subjects with even minor elevations of cTnI are at increased risk of premature MI (Palla et al 2011). When a patient with chest pain is seen in the emergency room, blood is routinely drawn to detect any rise in cardiac biomarker concentrations due to heart muscle damages.…”
Section: Introductionmentioning
confidence: 99%